Sulfur-rich colloidal nickel sulfides as bifunctional catalyst for all-solid-state, flexible and rechargeable Zn-air batteries - Sumboja, Afriyanti (2021)
Earth-abundant and high-performance catalysts for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) are highly desirable in development of energy-efficient rechargeable Zn-air batteries. In this work, sulfur-rich colloidal nickel sulfides (NiSₓ) are prepared as OER/ORR bifunctional catalysts via a two-step hydrothermal process. The NiSₓ nanoparticles (NPs) with large surface area show high OER activity and excellent stability, as evidenced by low overpotential of 301 mV, small Tafel slope of 41 mV dec⁻¹ and high stability over 20 h of chronopotentiometry test. Due to their sulfur-rich nature (i. e. Ni₃S₄ and NiS₂), the obtained NiSₓ also exhibit good ORR activity. The introduction of graphene oxide (GO) in the starting materials leads to the formation of a composite catalyst composed of conductive sulfur-doped reduced graphene oxide (S-rGO) and NiSₓ. A high ORR onset potential of 0.91 V (vs. RHE) is obtained from the sulfur-rich NiSₓ NPs coupled with the S-rGO which facilitates the electron-transfer and furnishes the bifunctional catalytic activity. Rechargeable Zn-air batteries with NiSₓ/S-rGO bifunctional catalyst deliver stable charge and discharge voltages of 2.1 and 1.1 V over 590 cycles. Furthermore, all-solid-state and foldable Zn-air batteries using pliable and robust air cathodes of NiSₓ/S-rGO show similar voltage profile as their non-foldable counterparts. The foldable batteries exhibit stable cycling performance for up to 120 discharge/charge cycles at either flat or folded state, proving their high electrochemical and mechanical stability.